The Effect of Covid-19 Vaccines on Menstrual cycle in selected Bangladeshi Female Population (Bangladesh Pharmaceutical Journal, 2024)
The pandemic associated with the coronavirus disease hit Bangladesh in the year of early 2020, which was a part of the global pandemic caused by SARS-CoV-2. Six vaccines, namely Moderna, Pfizer, Covishield, Sinopharm, Sinovac and Janssen out of the eight vaccines approved by WHO, were received by the Bangladeshi people. A cross-sectional online survey comprising a descriptive questionnaire was carried out to find the effect of Covid vaccine on menstrual cycle. The longer, shorter or absence of menstrual cycles and any changes in menstrual flow were taken under consideration during the survey. The majority of the respondents  (82.5%)  was  of  20-30  years  old  females.  Among  the  total  309  responders,  210  women  experienced  vaccine associated side effects while fever was experienced by 36.5%, 19.1% experienced fatigue and 21.4% was reported to suffer from headache. Muscle and joint aches as well as pain, swelling and redness were noted to be 38.5% (most common) and 26.4%, respectively  among  others.  Statistically  significant  (p